2009
DOI: 10.1590/s1807-59322009000500010
|View full text |Cite
|
Sign up to set email alerts
|

Retinoblastoma: A Three-Year-Study at a Brazilian Medical School Hospital

Abstract: OBJECTIVE: To present the characteristics and treatment outcomes of patients with retinoblastoma. METHODS: A retrospective case series was conducted to review the records of all new patients diagnosed with retinoblastoma between 2003 and 2005. Eyes with early disease, or advanced disease with potential vision were treated with chemotherapy (carboplatin and etoposide) in conjunction with early local therapy (laser or cryo). Radiotherapy was used in cases where the disease did not respond to the above protocols … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
17
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(25 citation statements)
references
References 28 publications
7
17
1
Order By: Relevance
“…Our study shows a male predominance (62%), which is similar to the gender distribution shown in reports from Mexico [10] (52.4%), Mali [16] (54.5%), Egypt [17] (60.25), and Jordan [18] (70.0%). There is a definite regional bias in studies from our country as males were generally preferred for treatment in earlier studies as well [3].…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…Our study shows a male predominance (62%), which is similar to the gender distribution shown in reports from Mexico [10] (52.4%), Mali [16] (54.5%), Egypt [17] (60.25), and Jordan [18] (70.0%). There is a definite regional bias in studies from our country as males were generally preferred for treatment in earlier studies as well [3].…”
Section: Discussionsupporting
confidence: 89%
“…HDI refers to a statistical measure of life expectancy, education, and income per capita used to rank the countries into 4 tiers of human development namely very high/high/medium/poor. In countries with very high HDI, the average age at presentation is earlier with increasing numbers of affected children less than 1 year of age [17,18]. The advanced age at presentation in our study can be attributed to the fact that nearly 12.9% of the patients belonged to the lower socioeconomic strata and more than 50% were from a rural population.…”
Section: Discussionmentioning
confidence: 58%
See 1 more Smart Citation
“…For unilateral disease, eyes falling under category D and E have neither potential for visual improvement nor conservative treatment options. Hence, enucleation remains the mainstay of treatment in most Southeast Asian settings (Aung et al, 2009, Bonanomi et al, 2009Reddy and Anusya, 2010), as was observed in the current study. Chemotherapy was administered post-enucleation in eyes with invasion into deep choroid and beyond.…”
Section: Discussionsupporting
confidence: 65%
“…This retinal tumor causes vision loss and can become life threatening if not treated [3,4]. The 10-year survival rate is 93% in the US [5], but ranges from 40% in low income countries to 79% in upper-middle income countries [6].…”
Section: Introductionmentioning
confidence: 99%